Angiogenesis effects of dental stem cells cultured on polymer scaffolds - Nur Najmi Ma; Noor Hasila Ad; Fazren Azmi; Thanaphum Osathanon; Rohaya Megat Abdul Wahab; Farinawati Yazid (Penerbit Universiti Kebangsaan Malaysia, 2025)
Following the PRISMA-ScR guidelines, three electronic databases were searched (PubMed, Scopus and Web of Science) to identify the related studies using specific keywords and terms. The abstracts were evaluated for inclusion and exclusion criteria. The included publications were descriptively analysed. Out of 296 articles found, only nine were included for analysis. The objective of this study was to assess the angiogenesis effects of dental stem cells cultured in a polymer scaffold by evaluating their ability to promote blood vessel formation, cell viability, and tissue regeneration, thereby providing insights into their potential therapeutic applications in regenerative medicine. Previous studies mainly focused on polymer scaffold research, neglecting the crucial aspect of angiogenesis in pulp regeneration. Despite DPSCs' versatility in bone regeneration, more research is needed to understand their relationship with angiogenesis. The untapped potential of DPSCs in promoting blood vessel formation and tissue regeneration requires further exploration. Limited investigation exists on how the combination of stem cell, angiogenic, and dentin markers affects angiogenesis in DPSCs. The morphological changes DPSCs undergo in scaffold environments and the gene/protein expression analyses in DPSCs on scaffolds with angiogenic factors are areas that still need exploration. This research gap holds promise for enhanced understanding and advancement in tissue engineering and regenerative medicine, particularly in DPSCs' connection with scaffolds and angiogenesis. There has been limited research on the interplay of DPSCs, polymer scaffolds, and angiogenesis, with unexplored combined consequences on tissue regeneration. Scaffold-based techniques to investigate angiogenesis with DPSCs are uncommon. Further research might transform tissue engineering and regenerative medicine, spanning beyond dentistry.